Argamassa com adição de resíduo de poliuretano: propriedades mecânicas e térmicas - Sena, Priscila Lopes dos Santos de (2019)
The civil construction sector has great relevance in the context of environmental crisis and waste generation, since, in addition to using a lot of raw material, it also presents high rates of discards. The incorporation of several types of residues, mainly in mortars and concretes, products with wide applicability in the sector, has been shown as a viable solution for the saving of natural resources, as well as for the correct destination of this waste. The polyurethane residue from the manufacture of surfboards has potential for application in civil construction. Therefore, this research had as main objective the analysis of the influence of the addition of this residue on the mechanical and thermal properties of mixed mortar (cement, lime and sand) with different contents of incorporation. The mortars studied were produced with the incorporation of polyurethane residue in substitution of natural sand, commonly used aggregate. Characterization tests of the materials used for the production of mortar were carried out, using 50, 75 and 100% (AR50, AR75 and AR100, respectively) substitution contents of sand for polyurethane residue and a mortar without residue (AR00). The mortars produced were submitted to tests aimed at the verification and analysis of the mechanical and thermal properties, as well as the thermal performance through the heat exchanges. It was possible to verify the influence of the residue on the properties of the fresh state (the higher the substitution content, the greater the amount of water needed for the same consistency) and the hardened state (reduction of mechanical resistance and mass density at percentage of replacement). It was also possible to verify the reduction of the thermal conductivity values as the sand substitution content increased, giving the mortars studied a greater thermal insulation compared to the reference mortar.